Teaching English for Vocational Purposes in the Digital Era: A Review - Suswanto (International Journal of Advanced Science and Technology, 2020)
English for Vocational Purposes (EVP) has gained popularity under the umbrella of English for Practical Uses (ESP), as more and more English-language services are targeted for those who want to study English related to their vocation. The ultimate aim of ESP teaching is to help professional learners perform well in workplaces or higher education vocational environments where English acts as a contact tool. A emerging question has also emerged as to whether ESP teachers can teach material or language, or both material and language. This chapter explores core aspects of EVP teaching as a answer to this question. The chapter’s core aim is to provide theoretical and realistic guidelines for ESP practitioners to plan and execute EVP teaching in the sense of studying English as an additional language.